Impact of health care organization on surgical lung cancer care. (September 2019) - Heineman, D.J.; Hoeijmakers, F.; Beck, N.; Dickhoff, C.; Daniels, J.M.; Schreurs, W.H.; Jakobsen, E.
Highlights: Healthcare is organized in a different way in Denmark and the Netherlands. Mortality of NSCLC surgery is low in both countries in the period 2013–2016. In the Netherlands there were more patients with a complicated course after surgery. Accuracy between clinical and pathological stage was around 53% in both countries. We should pursue uniform definitions of endpoints in national datasets. Abstract: Objectives: Organization and governance of national healthcare might play an important role in decision-making and outcomes in patients with lung cancer. Both Denmark and the Netherlands have a high level of healthcare but a different financial coverage, governance and level of centralization. By using both national databases we analyzed the consequences of these differences on patterns of care and outcomes with a focus on morbidity, mortality and clinical staging. Materials and methods: General numbers on both healthcare systems were requested. All patients who had surgery for lung cancer from 2013 to 2016 were included. Mortality, morbidity and clinical staging were analyzed for patients with NSCLC without metastases, only one operation and no neo-adjuvant therapy. Results: In 2016 annual budget as share of gross national product was 10.4% for both countries. In Denmark 4 hospitals performed lung surgery in 2016, compared to 43 hospitals in the Netherlands. We included 4030 Danish and 8286 Dutch patients. In the subgroup 30-day mortality was 1.5% in Denmark compared to 1.9% in the Netherlands. The percentage of patients with a complicated course was 24.4% and 34.8% respectively (p < 0.05). Accuracy between cTNM and pTNM was 53.0% in Denmark and 52.9% in the Netherlands. Conclusion: Surgery for lung cancer is at a high level in both countries, reflected by low mortality-rates. Centralization has been implemented successfully in Denmark, which might explain the lower rate of patients with a complicated post-operative course, although different definitions preclude firm conclusions. In both countries correct clinical staging of lung cancer remains a challenge.